Playing for Malaya a Eurasian family in the Pacific War - Kenneison, Rebecca (NUS Press, 2012)
One of the many gaps in Reggie's account of his family was that his mother was Eurasian. When Rebecca Kenneison discovered this omission after his death, she set out to learn more about her many relatives on the other side of the world. Her voyage of discovery is compelling in itself, but 'Playing for Malaya' has a much larger purpose. Set in the 1930s and 1940s, it recounts the experiences of an extended Eurasian family during the invasion and occupation of Malaya by the Japanese. Colonial society considered Eurasians insufficiently European to be treated as British, but they seemed all too European to the Japanese, who subjected the Eurasian community to discrimination and considerable violence. Many Eurasians, including members of this extended family, supported the Allied cause, and their wartime experiences are an extraordinary account of tragedy, heroism and endurance, presented here with great eloquence and clarity.